A sodium chromite sodium supplement with core-shell structure and a preparation method thereof
Patent Information
- Application Number
- CN202611497321.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-24
- Publication Date
- 2026-10-30
AI Technical Summary
现有表面包覆技术(如碳包覆等)采用的包覆层会物理约束内核在高压下发生的不可逆相变,抑制晶格体积变化,导致补钠容量无法充分释放
[0031]与现有技术相比,本发明上述技术方案中的一个或者多个至少能实现以下有益效果之一:
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery materials technology, specifically relating to sodium replenishment agents for sodium-ion batteries and their preparation methods. Background Technology
[0002] Sodium-ion batteries are considered an important technology for large-scale energy storage and low-speed electric vehicles due to the abundance and low cost of sodium resources. However, during the first charge of a sodium-ion battery, the SEI film formed on the negative electrode surface irreversibly consumes a large number of active sodium ions, resulting in a low initial coulombic efficiency, which severely limits the energy density and cycle performance of sodium-ion batteries.
[0003] Self-sacrificing sodium-compensating additives for positive electrodes have become the most promising pre-sodiumification route for industrialization due to their ease of operation and lack of the need for additional equipment. Sodium chromite (NaCrO2), as an O3-type layered oxide material, was initially mainly studied as a positive electrode material for sodium-ion batteries. Later, researchers used NaCrO2 as a self-sacrificing sodium compensation additive, utilizing its irreversible phase transition in the high-voltage region to provide an irreversible capacity of up to 230 mAh / g to compensate for the active sodium ions consumed in the formation of the SEI film in the negative electrode. However, the sodium-compensating structure of NaCrO2 in the highly desodium-depleted state collapses violently and disordered under high pressure, resulting in significant strain and stress within the material. This stress is caused by structural collapse. NaCrO2 undergoes multiple phase transitions during desodiumification, ultimately leading to chemical instability and mechanical deformation. This mechanical deformation may cause particle cracking and pulverization. Cracked particles generate numerous microcracks, which provide physical pathways for the growth of sodium dendrites in subsequent cycles. Dendrites penetrate the electrodes and puncture the separator along the cracks, ultimately leading to problems such as short circuits in the battery.
[0004] NaCrO2, as a sodium supplement, suffers from structural instability under high pressure and is prone to side reactions with the electrolyte. Existing technologies mainly employ the following improvement schemes: (I) Doping Modification. The structure is stabilized by introducing dopants into the NaCrO2 lattice. For example, CN115818716A discloses a doped and modified sodium chromite and its preparation method. Hexavalent chromium salts are mixed with doping modifiers (including metal cations such as calcium, titanium, vanadium, manganese, iron, cobalt, nickel, copper, and zinc), and a reduction reaction is carried out in a molten alkaline environment to achieve a uniform distribution of dopants. Furthermore, some researchers have enhanced the structural stability of materials by doping calcium at sodium sites. Studies have found that calcium doping not only improves cycling performance but also unexpectedly enhances the material's air stability.
[0005] However, while this uniform doping stabilizes the crystal structure overall, it also suppresses the irreversible phase transition of the material, leading to a decrease in sodium replenishment capacity. For sodium replenishers, the core function is to undergo an irreversible phase transition under high pressure to release sodium ions; uniform doping weakens this function, creating a contradiction where a stable structure is achieved at the expense of sodium replenishment capacity.
[0006] (ii) Surface Coating. A coating layer is constructed on the surface of NaCrO2 particles to block electrolyte contact and suppress side reactions. For example, CN115863609A discloses a carbon-coated sodium chromite material and its preparation method; CN121172308A discloses a sodium supplement agent, comprising: a core, the core comprising a sodium supplement material; and a coating layer comprising carbon material, metal atoms, and non-metal atoms, wherein the metal atoms and non-metal atoms are located in the carbon material; wherein the metal atoms include at least one of noble metal atoms and transition metal atoms.
[0007] The aforementioned surface coatings suffer from the problems of inhibiting sodium replenishment capacity release and increasing dead mass. Existing surface coating technologies (such as carbon coating) use coating layers that physically constrain the irreversible phase transition of the core under high pressure, suppressing lattice volume changes and resulting in insufficient release of sodium replenishment capacity. Furthermore, the coating layer itself does not contribute to sodium replenishment capacity, increasing inactive mass and diluting the sodium replenishment efficiency of the sodium replenishing agent, thus reducing the sodium replenishment effect at the same addition amount.
[0008] To address the problems existing in the current technology, it is imperative to provide a sodium supplement agent that can significantly improve the structural and interfacial stability of the material while ensuring high sodium supplementation capacity. Summary of the Invention
[0009] In a first aspect, the present invention provides a core-shell structured sodium chromite supplement, the supplement comprising a core and a shell, wherein the core is pure-phase sodium chromite having an O3-type layered structure; and the shell is doped and modified sodium chromite, the general chemical formula of which is NaM. x Cr 1-x O2, where M is a doped metal cation, 0 < x ≤ 0.15.
[0010] Furthermore, the mass percentage of the doped metal cation is 0.5%-0.8%, preferably 1%-5%.
[0011] Furthermore, the radius of the kernel is 5-30 μm, preferably 10-25 μm.
[0012] Furthermore, the thickness of the shell layer is 1-50 nm, preferably 2-20 nm.
[0013] Furthermore, the doped metal cation M includes strontium ions (Sr).2+ ), calcium ions (Ca 2+ ), titanium ions (Ti 4+ ), Vanadium ions (V 5+ ), manganese ions (Mn) 4+ ), iron ions (Fe 3+ ), cobalt ions (Co) 3+ Nickel ions (Ni) 2+ ), copper ions (Cu) 2+ ), zinc ions (Zn 2+ ), aluminum ions (Al) 3+ Any one or a combination of at least two of the following. Preferably, the doped metal cation M is a nickel ion (Ni... 2+ ), aluminum ions (Al) 3+ One of them.
[0014] Secondly, the present invention provides a method for preparing the above-mentioned sodium chromite supplement, comprising the following steps: Step S1, preparing doped modified sodium chromite powder: ball milling and mixing trivalent chromium source, sodium source and modifier containing doped metal cation M to obtain a mixture; sintering the mixture under an inert atmosphere to obtain a sintered material; crushing and grinding the sintered material to obtain doped modified sodium chromite powder with a particle size D50 of 60-300nm. Step S2, Core-shell structure composite: Pure phase sodium chromite powder with O3 type layered structure and particle size D50 of 5-30 μm is ball-milled and mixed with doped and modified sodium chromite powder with particle size D50 of 60-300 nm; the ball-milled material is dried under vacuum and then heat-treated under an inert atmosphere. Step S3: Wash and dry the product obtained in step S2 to obtain a core-shell structured sodium chromite sodium supplement.
[0015] Furthermore, the trivalent chromium source is chromium trioxide (Cr2O3), and the sodium source is sodium carbonate (Na2CO3).
[0016] Furthermore, the molar ratio of the doped metal cation M in the modifier, the sodium ion in the sodium source, and the chromium ion in the trivalent chromium source is 0.01-0.15:1.0-1.1:1.
[0017] Furthermore, the modifier is at least one of sulfate, carbonate, nitrate, oxide, and hydroxide containing a doped metal cation M.
[0018] Furthermore, the ball milling speed in step S1 is 400-600 rpm.
[0019] Furthermore, the ball milling mixing time in step S1 is 6-12 hours.
[0020] Furthermore, the sintering temperature in step S1 is 700-950℃, preferably 750-900℃.
[0021] Furthermore, the sintering time in step S1 is 2-10 hours, preferably 3-8 hours.
[0022] Furthermore, in step S2, the mass ratio of pure-phase sodium chromite powder with an O3-type layered structure to doped and modified sodium chromite powder is 5-20:1, preferably 10-15:1.
[0023] Furthermore, in step S2, the rotation speed of the ball mill mixing is 200-400 rpm.
[0024] Furthermore, in step S2, the ball milling mixing time is 2-4 hours.
[0025] Furthermore, in step S2, the temperature of the vacuum drying is 60-80°C.
[0026] Furthermore, in step S2, the temperature of the heat treatment is 700-950℃.
[0027] Furthermore, in step S2, the heat treatment time is 2-8 hours.
[0028] Furthermore, ball milling media are added during the ball milling process.
[0029] Furthermore, the inert atmosphere is at least one of nitrogen and argon.
[0030] In the preparation of sodium chromite supplements, increasing the particle size difference between the core and shell materials allows for selective coating. When the large core particles (micrometer-sized) and the small shell particles (nanometer-sized) are mixed and ball-milled, the smaller particles are more easily embedded and adhered to the surface of the larger particles under mechanical impact. The core size can be selected as needed, and the shell thickness can be controlled by adjusting the mass ratio of doped and modified sodium chromite powder to pure-phase sodium chromite powder. The more doped and modified sodium chromite powder added, the thicker the shell layer.
[0031] Compared with the prior art, one or more of the above-described technical solutions of the present invention can achieve at least one of the following beneficial effects: This invention achieves precise functional partitioning through a homogeneous core-shell structure design with a pure-phase core and a doped outer shell. The core remains pure-phase, its lattice unconstrained by artificially enhanced bond energies under high pressure, allowing chromium ions to migrate freely and the layered structure to fully collapse, thus ensuring the complete occurrence of irreversible phase transitions and releasing a high capacity of active sodium ions (≥220 mAh / g). The shell, through the incorporation of dopants into the lattice, forms stronger MO bonds, effectively suppressing chromium ion migration and irreversible phase transitions from within the bulk phase. By confining the doping to the shell, this invention stabilizes the shell structure from within the bulk phase while ensuring a high sodium replenishment capacity in the core.
[0032] In this invention, the shell and core are made of the same material (doped NaCrO2), with no lattice mismatch or difference in thermal expansion coefficients at the interface. More importantly, the shell of this invention achieves stability through chemical doping, rather than through physical coating. Specifically, after the dopant element enters the shell lattice, it suppresses chromium ion migration and irreversible phase transitions in the shell region by forming stronger MO bonds, allowing the shell to maintain structural integrity under high voltage. This is an intrinsic stabilization achieved by changing the chemical bond energy, rather than through external physical forces. Therefore, although the doped shell itself does not undergo an irreversible phase transition, it does not hinder the volume change and structural collapse of the core, allowing the core's sodium replenishment capacity to be fully released. At the same time, this complete doped shell acts as a physical barrier, isolating the highly active pure-phase core from direct contact with the electrolyte, significantly suppressing lattice oxygen extraction and the generation of gases such as CO2. Therefore, this invention achieves a significant reduction in gas production without sacrificing sodium replenishment capacity.
[0033] In this invention, heat treatment causes doped sodium chromite powder to grow in situ on the surface of pure-phase sodium chromite powder, forming a doped shell. In-situ growth results in chemical bonding between the shell and the core, leading to high interfacial strength and a defect-free interface. Furthermore, the process is highly compatible with traditional solid-state methods, requiring no complex equipment and facilitating large-scale production.
[0034] In this invention, since the shell accounts for a very small proportion of the overall particle (the shell thickness is only 1-50 nm, while the core particle size is 5-30 μm), the inhibitory effect of shell doping on the total sodium replenishment capacity is minimized.
[0035] The doped shell of this invention forms a chemically stable protective layer on the particle surface. The introduction of the dopant element alters the surface chemical state, reduces the activity of surface alkaline sites, and decreases the formation of residual alkali. Simultaneously, the doped shell acts as a physical barrier, preventing direct contact between airborne moisture and CO2 and the core. Detailed Implementation
[0036] To facilitate understanding of the present invention, the present invention will be described more fully and in detail below with reference to preferred embodiments, but the scope of protection of the present invention is not limited to the following specific embodiments.
[0037] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.
[0038] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.
[0039] In the specific implementation of this invention, pure-phase sodium chromite with an O3-type layered structure is prepared by the following method: Sodium carbonate and chromium trioxide were ball-milled at a sodium to chromium molar ratio of (1.0–1.1):1. The ball-to-material ratio was (10–20):1, and the mixture was ball-milled at 300–400 rpm for 4–8 hours. The ball-milled slurry was then vacuum-dried at 60–80 °C for 6–12 hours and sintered at 800–1000 °C for 5–15 hours under an inert atmosphere to obtain pure-phase O3–NaCrO2 powder. The D50 of the pure-phase O3–NaCrO2 powder was 5–30 μm.
[0040] Example 1 Step 1: Prepare doped and modified sodium chromite powder: 3.04 g of chromium trioxide, 2.16 g of sodium carbonate, and 0.212 g of dopant strontium nitrate (Sr(NO3)2) were added to a ball mill jar along with grinding media and ball-milled at 400 rpm for 12 hours to obtain a mixture. The mixture was sintered at 700℃ for 10 hours to obtain a sintered product. The sintered material was crushed and ground to a particle size D50 of 60-300 nm to obtain a doped powder.
[0041] Step 2: Preparation of sodium chromite supplement with a core-shell structure: 50g of pure phase O3–NaCrO2 powder, 5g of doped powder, and grinding media were ball-milled in a ball mill at 200 rpm for 4 hours. The ball-milled material was then vacuum-dried at 60℃. The dried material was then heat-treated at 700℃ for 8 hours under a nitrogen inert atmosphere. The resulting product was washed and dried to obtain a sodium supplement.
[0042] The steps of Examples 2-11 are the same as those in Example 1. The specific parameters for each example are shown in Table 1.
[0043] Table 1. Parameter data for Examples 1-11 Performance testing: I. Half-cell test of pure sodium supplement 1. Electrode preparation Sodium supplement (the sodium supplement in Examples 1-11 and pure phase NaCrO2) was mixed with conductive agent Super P and binder PVDF at a mass ratio of 7:2:1. The mixture was stirred into a uniform slurry using N-methylpyrrolidone (NMP) as a solvent. This slurry was coated onto aluminum foil, dried at 80°C for 2 hours under forced air and then vacuum-dried at 120°C for 12 hours. The resulting material was then cut into circular positive electrode sheets with a diameter of 12 mm. The active material loading was controlled at 1.0-2.0 mg / cm².
[0044] 2. Button cell battery assembly Using a sodium metal sheet as the negative electrode, a glass fiber membrane as the separator, and a 1 mol / L NaPF6 EC / DEC (volume ratio 1:1, containing 2% FEC) solution as the electrolyte, CR2032 coin cells were assembled in an argon glove box and allowed to stand for 8-12 hours before testing.
[0045] 3. Test methods and conditions All electrochemical tests were performed on the Blue Electric test system under constant temperature conditions of 25°C.
[0046] For a sodium-replenished half-cell: charge at a constant current of 0.066C to 4.20V, then charge at a constant voltage of 4.0V until the current ≤0.01C, let stand for 2 min, and discharge at a constant current of 0.1C to 2.0V. Record the initial charge specific capacity Cc and discharge specific capacity Cd, and calculate the initial coulombic efficiency ICE = Cd / Cc × 100%.
[0047] 4. Test Results Table 2. First charge-discharge data of sodium-supplemented half-cells As shown in Table 2, the sodium replenishing agents of the 11 embodiments of this invention exhibited a high initial charge specific capacity of 216-226 mAh / g and an irreversible capacity of 170-174 mAh / g in pure half-cell tests. This high irreversible capacity originates from the irreversible phase transition that occurs in the pure-phase core of the core-shell structure under high pressure, where chromium ions migrate from the CrO2 layer to the sodium layer, irreversibly transforming the layered structure into the rock salt phase. Since the sodium replenishing agent is a one-time sacrificial agent and lacks reversible sodium intercalation capability, its discharge capacity and initial efficiency are relatively low (20.4-24.3%), which is entirely consistent with the designed function of the sodium replenishing agent. In contrast, while the pure-phase NaCrO2 exhibits the highest initial charge capacity (228 mAh / g) and irreversible capacity (166 mAh / g), its discharge capacity is also the highest (62 mAh / g), indicating that some of the extracted sodium ions can still be re-intercalated. This actually means that the irreversible phase transition is not thorough enough, and the sodium replenishment efficiency is actually lower than that of the core-shell structure sample.
[0048] II. Composite Positive Electrode Half-Cell Test 1. Electrode preparation The sodium supplement prepared in Examples 1-11 was mixed with NFPP (composite sodium iron phosphate) at a mass ratio of 4:96 to form a composite active material. The composite active material: Super P:PVDF = 70:20:10 was used to prepare the slurry, which was then coated and assembled into half-cells. At the same time, a blank control cell was prepared using pure NFPP as the active material.
[0049] 2. Test methods and conditions The composite cathode half-cell and blank cell were tested using the same procedure: charged to 4.0 V at a constant current of 0.1C, allowed to stand for 2 minutes, and discharged to 1.5 V at a constant current of 0.1C. The initial charge specific capacity and discharge specific capacity were recorded, and the initial coulombic efficiency was calculated.
[0050] Cyclic performance test: After the first charge and discharge, charge at a constant current and constant voltage of 0.5C to 4.0V (cutoff current 0.02C), then discharge at a constant current of 0.5C to 1.5V, cycle 200 times, record the discharge specific capacity of each cycle, and calculate the capacity retention rate.
[0051] 3. Test Results Table 3 Performance Comparison of Composite Cathode Half-Cells As shown in Table 3, when the sodium replenisher of the present invention is added to the NFPP positive electrode at a ratio of 4%, the initial coulombic efficiency of the battery increases significantly from 86.0% to 95.6-96.0%, indicating that the large amount of active sodium released by the sodium replenisher during the first charge cycle effectively compensates for the irreversible sodium loss caused by the formation of SEI and side reactions at the negative electrode. Simultaneously, the capacity retention rate after 200 cycles increases from 89.2% to 93.2-95.8%, demonstrating that the core-shell structure sodium replenisher of the present invention has excellent long-term sodium replenishment capability and cycle stability.
[0052] In comparison, the initial efficiency (94.4%) and cycle retention (91.5%) of the pure-phase NaCrO2 sodium supplement were both lower than those of the embodiments of the present invention, fully demonstrating the significant gain of the synergistic design of core-shell structure with sacrificial core sodium supplementation and stable outer shell protection. The shell layer is doped with elements (such as Al) 3+ Ni 2+ (etc.) enter the crystal lattice to form stronger M–O bonds, effectively suppressing chromium ion migration and irreversible phase transition from the bulk phase, while also acting as a physical barrier to prevent direct contact between the electrolyte and the highly active core.
[0053] Furthermore, based on the data in Tables 2 and 3, Al-doped (Example 11) and Ni-doped (Example 8) showed the best performance: Example 11 (Al-doped): initial charge capacity 226 mAh / g, composite cathode initial efficiency 96.0%, and 200-cycle retention rate 95.8%; Example 8 (Ni-doped): initial charge capacity 224 mAh / g, composite cathode initial efficiency 95.8%, and 200-cycle retention rate 95.3%. 3+ and Ni 2+ After entering the shell lattice, it forms stronger M–O bonds, effectively pinning lattice oxygen and inhibiting Cr ion migration.
[0054] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A core-shell structured sodium chromite sodium supplement, characterized in that, The sodium supplement comprises a core and a shell. The core is pure-phase sodium chromite with an O3-type layered structure; the shell is doped and modified sodium chromite, and the general chemical formula of the shell material is NaM. x Cr 1-x O2, where M is a doped metal cation, including strontium ions (Sr). 2+ ), calcium ions (Ca 2+ ), titanium ions (Ti 4+ ), Vanadium ions (V 5+ ), manganese ions (Mn) 4+ ), iron ions (Fe 3+ ), cobalt ions (Co) 3+ Nickel ions (Ni) 2+ ), copper ions (Cu) 2 + ), zinc ions (Zn 2+ ), aluminum ions (Al) 3+ Any combination of one or at least two of the following, 0 < x ≤ 0.
15.
2. The core-shell structured sodium chromite sodium supplement as described in claim 1, characterized in that, It has at least one of the following technical features: (1) The mass percentage of the doped metal cation is 0.5%-0.8%; (2) The radius of the kernel is 5-30 μm; (3) The thickness of the shell is 1-50 nm.
3. A method for preparing a core-shell structured sodium chromite sodium supplement as described in claim 1 or 2, characterized in that, Includes the following steps: Step S1, preparing doped modified sodium chromite powder: ball milling and mixing trivalent chromium source, sodium source and modifier containing doped metal cation M to obtain a mixture; sintering the mixture under an inert atmosphere to obtain a sintered material; crushing and grinding the sintered material to obtain doped modified sodium chromite powder with a particle size D50 of 60-300nm. Step S2, Core-shell structure composite: Pure phase sodium chromite powder with O3 type layered structure and particle size D50 of 5-30 μm is ball-milled and mixed with doped and modified sodium chromite powder with particle size D50 of 60-300 nm; the ball-milled material is dried under vacuum and then heat-treated under an inert atmosphere. Step S3: Wash and dry the product obtained in step S2 to obtain a core-shell structured sodium chromite sodium supplement.
4. The preparation method according to claim 3, characterized in that, The trivalent chromium source is chromium trioxide (Cr2O3), and the sodium source is sodium carbonate (Na2CO3).
5. The preparation method according to claim 3 or 4, characterized in that, The molar ratio of the doped metal cation M in the modifier, the sodium ion in the sodium source, and the chromium ion in the trivalent chromium source is 0.01-0.15:1.0-1.1:
1.
6. The preparation method according to claim 3, characterized in that, The modifier is at least one of sulfate, carbonate, nitrate, oxide, and hydroxide containing a doped metal cation M.
7. The preparation method according to claim 3, characterized in that, It has at least one of the following technical features: (1) The ball milling speed in step S1 is 400-600 rpm; (2) The ball milling mixing time in step S1 is 6-12 hours; (3) The sintering temperature in step S1 is 700-950℃; (4) The sintering time in step S1 is 2-10h.
8. The preparation method according to claim 3, characterized in that, It has at least one of the following technical features: (1) In step S2, the mass ratio of pure phase sodium chromite powder with O3 type layered structure and particle size D50 of 5-30 μm to doped modified sodium chromite powder with particle size D50 of 60-300 nm is 5-20:
1. (2) In step S2, the rotation speed of the ball mill mixing is 200-400 rpm; (3) In step S2, the ball milling mixing time is 2-4 hours; (4) In step S2, the temperature of the vacuum drying is 60-80℃; (5) In step S2, the temperature of the heat treatment is 700-950℃; (6) In step S2, the heat treatment time is 2-8 hours.
9. The preparation method according to claim 3, characterized in that, The ball milling media are added during the ball milling process; the inert atmosphere is at least one of nitrogen and argon.
Citation Information
Patent Citations
Sodium supplementing agent, sodium ion battery, electronic equipment and preparation method of sodium supplementing agent
CN121172308A
